HLA-specific polymorphisms in HIV-1 Gag and their association with viral load in chronic untreated infection - Brumme, Zabrina L.; Tao, Iris; Szeto, Sharon; Brumme, Chanson J.; Carlson, Jonathan M.; Chan, Dennison; Kadie, Carl; Frahm, Nicole; Brander, Christian; Walker, Bruce; Heckerman, David; Harrigan, P. Richard (2009)
Objective: Selection of specific human leukocyte antigen (HLA)-restricted cytotoxic T-lymphocyte (CTL) escape mutations in key Gag epitopes has been associated with loss of HIV immune control on an individual basis. Here we undertake a population-based identification of HLA-associated polymorphisms in Gag and investigate their relationship with plasma viral load. Design: Cross-sectional analysis of 567 chronically HIV subtype B-infected, treatment-naive individuals. Methods: HLA class I-associated Gag substitutions were identified using phylogenetically corrected analysis methods featuring a multivariate adjustment for HLA linkage disequilibrium and a q-value correction for multiple tests. Presence of HLA-associated substitutions and markers of HIV disease status were correlated using Spearman's rank test. Results: We have created a gene-wide map of HLA class I-associated substitutions in HIV-1 subtype B Gag. This features 111 HLA-associated substitutions occurring at 51 of 500 Gag codons, more than 50% of which occur within published and/or putative HLA-restricted CTL epitopes. A modest inverse correlation was observed between the total number of HLA-associated Gag polymorphic sites within each individual and plasma viral load in chronic untreated infection (R = −0.17, P < 0.0001), supporting the hypothesis that a broad ability to target Gag in vivo contributes to viral control. A modest positive correlation was observed between the proportion of these sites exhibiting HLA-associated substitutions and plasma viral load (R = 0.09, P = 0.03), consistent with a loss of viremia control with the accumulation of CTL escape mutations. Conclusion: Results contribute to our understanding of immune-driven viral adaptation and suggest that the accumulation of CTL escape mutations in Gag results in clinically detectable consequences at the population level. These data have implications for HIV vaccines.